1999
DOI: 10.1016/s0022-2860(98)00794-7
|View full text |Cite
|
Sign up to set email alerts
|

A concerted SCF-MO ab initio and vibrational spectroscopic study of the conformational isomerism in 2-aminoethanol

Abstract: Conformational isomerism in isolated and liquid 2-aminoethanol was investigated by a concerted molecular orbital and vibrational spectroscopic approach. The molecular structures, relative energies, dipole moments and vibrational spectra (both infrared and Raman) of the various possible conformers of the studied compound were calculated, using the extended 6-31G* basis set at the HF-SCF ab initio level of theory. The theoretical results were then used to interpret infrared and Raman data obtained under differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
51
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 61 publications
(63 citation statements)
references
References 25 publications
11
51
1
Order By: Relevance
“…As for 2AE and 2AP [3,5], and contrary to what was found for 3AP [4], temperature variation studies carried out on the pure liquid show that there are no detectable amounts of free monomeric molecules in the pure liquid 1AP. The different behavior of 3AP, when compared with the remaining aminoalcohols, has been correlated with the larger conformational exibility in 3AP, which leads to a more favorable OH Á Á Á N intramolecular hydrogen bonding interaction geometry [4,5,27].…”
Section: Liquid Phase Infrared and Raman Spectracontrasting
confidence: 60%
See 2 more Smart Citations
“…As for 2AE and 2AP [3,5], and contrary to what was found for 3AP [4], temperature variation studies carried out on the pure liquid show that there are no detectable amounts of free monomeric molecules in the pure liquid 1AP. The different behavior of 3AP, when compared with the remaining aminoalcohols, has been correlated with the larger conformational exibility in 3AP, which leads to a more favorable OH Á Á Á N intramolecular hydrogen bonding interaction geometry [4,5,27].…”
Section: Liquid Phase Infrared and Raman Spectracontrasting
confidence: 60%
“…In agreement with the strongest intramolecular OH Á Á Á N hydrogen bond present in the conformational ground state of 3AP, which reduces its tendency to aggregate, the spectroscopic data obtained for this molecule clearly show that monomers assuming this conformation are also present in detectable amounts in the pure liquid [4], while for 2AE and 2AP, where the intramolecular OH Á Á Á N hydrogen bonding is considerably weaker than in 3AP, no experimental evidence could be found for the presence of monomeric species in the pure liquids [3,5].…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…When comparing the glass-forming tendency of the two compounds, we can see from 40% to 45% (w/w) that 21AE is more effective than 31AP. This observation is backed up by quantum chemical calculations and matrix-isolation infrared experiments conducted on these compounds [12,31], which showed that the intramolecular hydrogen bonding of 31AP is stronger than in 21AE. A significant amount of intramolecularly bond monomers of 31AP was found for this compound in the pure liquid [12], clearly indicating that for this molecule intramolecular hydrogen bonding is of similar strength as intermolecular interactions.…”
Section: Stability Of the Wholly Amorphous State On Warmingmentioning
confidence: 87%
“…A significant amount of intramolecularly bond monomers of 31AP was found for this compound in the pure liquid [12], clearly indicating that for this molecule intramolecular hydrogen bonding is of similar strength as intermolecular interactions. As a result, 31AP is less able to create the hydrogen bonds with the water molecules required to disturb and inhibit ice nucleation than 21AE, where no evidence of the presence of intramolecularly bond monomers species was found in the liquid phase [31].…”
Section: Stability Of the Wholly Amorphous State On Warmingmentioning
confidence: 98%